Advances in the Extraction, Purification, Structural Characteristics and Biological Activities of Eleutherococcus senticosus Polysaccharides: A Promising Medicinal and Edible Resource With Development Value - Xiaojie Li; Xiaojie Li; Cai Chen; Cai Chen; Aijing Leng; Aijing Leng; Jialin Qu; Jialin Qu (Frontiers Media S.A., 2021)
In recent years, natural polysaccharides have received growing attention and interest in view of their values in food, medical, cosmetics and other fields. Eleutherococcus senticosus (E. senticosus) is a medicine and food homologous plant that possess anti-tumor, anti-inflammatory, central nervous system and cardiovascular protection, anti-radiation, enhancement of human microcirculation, improvement of physical fatigue effects, mainly based on lignans, flavonoids and coumarin types. E. senticosus polysaccharides (ESPS), act as a kind of polysaccharide extracted and isolated from the root and rhizome of E. senticosus, have been found in many applications of medicine and food for their unique biological activity. Nevertheless, the existing studies are mostly concerned with small molecules of E. senticosus, less attention is paid to polysaccharides. Moreover, the types and structural characterization of ESPS reported in existing literature were also not summarized. In this paper, the research progress of ESPS is reviewed from the aspects of extraction, separation, structural characterization and biological activity, future perspectives from points of efficient extraction, resource utilization and quality control standards were also proposed, which provide reference for the further development and utilization of ESPS.